Transient Global Amnesia (TGA): Younger Age and Absence of Cerebral Microangiopathy Are Potentially Predisposing Factors for TGA Recurrence - Andreas Rogalewski; Anne Beyer; Anja Friedrich; Jorge Plümer; Frédéric Zuhorn; Randolf Klingebiel; Friedrich G. Woermann; Christian G. Bien; Isabell Greeve; Wolf-Rüdiger Schäbitz (Frontiers in Neurology, 2021)
Background: Transient global amnesia (TGA) is defined by an acute memory disturbance of unclear etiology for a period of less than 24 h. TGA occurs as a single event in most cases. Prevalence rates of recurrent TGA vary widely from 5.4 to 27.1%. This retrospective study aimed to determine predictors for TGA recurrence.Methods: Cardiovascular risk profile and magnetic resonance imaging (MRI) of 340 hospitalized TGA patients between 2011 and 2020 were retrospectively analyzed. The median follow-up period amounted to 4.5 ± 2.7 years. Comparisons were made between TGA patients with and without subsequent recurrence.Results: TGA patients with subsequent recurrence were significantly younger (recurrent vs. single episode, 63.6 ± 8.6 years vs. 67.3 ± 10.5 years, p = 0.032) and showed a lower degree of cerebral microangiopathy compared to TGA patients without recurrence. The mean latency to recurrence was 3.0 years ± 2.1 years after the first episode. In a subgroup analysis, patients with at least five years of follow-up (N = 160, median follow-up period 7.0 ± 1.4 years) had a recurrence rate of 11.3%. A 24.5% risk of subsequent TGA recurrence in the following five years was determined for TGA patients up to 70 years of age without microangiopathic changes on MRI (Fazekas' score 0).Conclusion: Younger TGA patients without significant microangiopathy do have an increased recurrence risk. In turn, pre-existing cerebrovascular pathology, in the form of chronic hypertension and cerebral microangiopathy, seems to counteract TGA recurrence.